Violencia familiar y factores asociados - Chica Heredia, Kimberlyn Mishell (Machala : Universidad Técnica de Machala, 2019)
INTRODUCTION: Family Violence is one of the social problems of greater presentation and expression in our population. It is defined as any act of physical or psychological aggression, which occurs within a home. Among the main risk factors we have: experiencing abuse since childhood, substance abuse, economic limitation, among others. OBJECTIVE: To identify the risk factors associated with the presentation and expression of intrafamily violence in the population. MATERIALS AND METHODS: This is a retrospective study, with the acquisition of scientific evidence in the PUBMED, GOOGLE ACADEMICO and SCIELO databases, with Latin American and Central American articles (Ecuador, Peru, Colombia, Mexico, Costa Rica, El Salvador), published between 2000 and 2018, a review of the data and a summary of the conclusions was made. CONCLUSION: The presence of Family Violence, whether psychological, physical and sexual is a problem in general, that despite being present in all social classes, has greater expression in vulnerable classes and this is associated in large part with the greater consumption and substance abuse, which generates the triggering of aggressive attitudes within the home.
INTRODUCCION: La Violencia Familiar es uno de los problemas sociales de mayor presentacion y expresion en nuestra poblacion. Se define como cualquier acto de agresion fisica o psicologica, que se produce dentro de un hogar. Dentro de los principales factores de riesgo tenemos: experimentar abuso desde la infancia, el abuso de sustancias, limitacion economica, entre otros. OBJETIVO: Identificar los factores de riesgo asociados a la presentacion y expresion de la violencia intrafamiliar en la poblacion. MATERIALES Y METODOS: Es un estudio retrospectivo, con adquisición de evidencia científica en la base de datos PUBMED, GOOGLE ACADEMICO y SCIELO, con artículos latinoamericanos y centroamericanos (Ecuador, Peru, Colombia, Mexico, Costa Rica, El Salvador), Publicados entre 2000 y 2018 se realizó una revision de los datos y un resumen de las conclusiones. CONCLUSION: La presencia de Violencia Familiar, ya sea psiocologica, fisica y sexual es un problema en general, que a pesar de estar presnete en todas clases sociales, tiene mayor expresion en clases vulnerables y esto se asocia en gran parte por el mayor consumo y abuso de sustancias, lo cual genera el desencadenamiento de actitudes agresivas dento del hogar.
Keywords: FAMILIA; VIOLENCIA; FACTORES DE RIESGO